Pengaruh Penambahan Ekstrak Daun Kecombrang (Etlingera Elatior) sebagai Inhibitor Korosi Baja Karbon dalam Media Air Laut - Hayati, Ratnal; Sariadi, Sariadi; Yunus, Muhammad (Jurnal Teknologi, 2024)
Carbon steel is a type of metal that is widely used in industry. However, carbon steel has a weakness, namely that it corrodes easily. One way to control corrosion is by adding inhibitors. The use of organic inhibitors is preferred considering the negative impact of inorganic inhibitors. In this research, kecombrang leaf extract was used as organic inhibitors. The kecombrang leaf extract has the –OH and CH functional groups which can be adsorbed by metal surfaces and can inhibit corrosion. Determination of the rate of corrosion in carbon steel using the weight loss method in sea water media. The results of the research obtained that kecombrang leaves which got the best results using the weight loss method based on concentration variants, namely 0,1,3,5, and 7 mL and soaking times of 3, 6, 9, and 12 days, which shows that the corrosion rate decreases with increasing concentration of kecombrang leaf extract. In varying concentrations, the optimum inhibition efficiency was found at a concentration of 7 mL and at 12 days immersion time, namely 75.88% and the corrosion rate was 0.9735 mpy so this result was the best corrosion rate test. Analysis of the carbon steel surface using SEM shows that the carbon steel surface has been protected by a layer of kecombrang leaf extract inhibitor.